2016
DOI: 10.1177/1098612x15606774
|View full text |Cite
|
Sign up to set email alerts
|

Association of mineralisations in the stifle joint of domestic cats with degenerative joint disease and cranial cruciate ligament pathology

Abstract: Objectives The aim of the study was to evaluate the prevalence, size, location and appearance of mineralisations in feline stifle joints, and to evaluate their relationship with osteoarthritis and cranial cruciate ligament (CrCL) status. Methods Presence or absence, and size of mineralisations were determined from lateral stifle radiographs of 25 cats with CrCL rupture, and 44 cat cadavers without CrCL rupture. Mineralisations were classified as small, medium or large. Prevalence was compared between the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
2
8
1
Order By: Relevance
“…Mineralization was detected in the medial menisci of most stifle joints with OA and was also bilateral in most instances. Although the relationship between radiographic evidence of stifle mineralization and histopathological disease has shown a clear association (21,22), the radiographical evidence and orthopedic examination in this study showed no evidence of anterior cruciate ligament rupture. Therefore, we considered that this feature might be a characteristic of OA among domestic short-haired cats in Japan.…”
Section: Discussioncontrasting
confidence: 70%
“…Mineralization was detected in the medial menisci of most stifle joints with OA and was also bilateral in most instances. Although the relationship between radiographic evidence of stifle mineralization and histopathological disease has shown a clear association (21,22), the radiographical evidence and orthopedic examination in this study showed no evidence of anterior cruciate ligament rupture. Therefore, we considered that this feature might be a characteristic of OA among domestic short-haired cats in Japan.…”
Section: Discussioncontrasting
confidence: 70%
“…Cats were designated as osteoarthritic based on positive findings from the orthopaedic examination and radiography. The radiographic criteria used were marginal or periarticular osteophytes, subchondral bone sclerosis, subchondral bone lysis and cyst‐like lesions, articular mineralisations, increased volume of the soft tissue opacity structures of the joint, and remodelling of joint shape 5 24–26 …”
Section: Methodsmentioning
confidence: 99%
“…In particular, Voss reported that small mineralizations were usually confi ned to the medial meniscus while larger mineralizations tended to be located cranially to the menisci potentially associated with osteoarthritis and cranial cruciate ligament disease [30]. In this study, even cats had no history of major trauma and fi ve of them had large mineralization located cranially to the meniscus.…”
Section: Discussionmentioning
confidence: 60%